Pengembangan Bisnis UMKM "Toko Anugrah" Menggunakan Strategi Pemasaran Marketing Mix - Nurjanah, Yuanita; Rahmi, Vembri Aulia (VISA: Journal of Vision and Ideas, 2024)
The tight competition of retail businesses in the Gresik Regency area makes Anugrah stores must have a superior business strategy in order to survive and compete. This study aims to determine the marketing strategy that has been implemented and the application of the marketing mix at the store and find the right business strategy at the Anugrah store through marketing mix analysis. The research method used in this study uses a qualitative method with a phenomenological approach. The research was conducted with one owner, two employees and five customers of Anugrah shop on Jl. Education No. 2, Bunderan Village, Sidayu District, Gresik Regency. The results showed that the Anugrah shop has three marketing strategies in running its business and has implemented the marketing mix in the company's operational system.